BRAZILIAN ILLITERACY: DISCUSSING THE INSUFFICIENCY OF THE INSTITUTIONALIZED LITERACY PROCESS - Pavan Ribeiro Tebaldi, Evelin Louise; Lemes, Sebastiao de Souza [UNESP] (Univ Fed Sao Carlos, 2021)
In order to better understand brazilian illiteracy in the last four decades, this research proposed a comparative study between the profile of brazilian illiteracy in the 1980s, characterized by Azevedo (1997) as high, unequal and reluctant, and that of 2010, observing the transformations of that period, in which public policies sought the universalization of basic education. For this purpose, a documentary research, based on the National Demographic Census (1980,1991, 2000, 2010), and a bibliographic research, based on Azevedo (1997), Ferrari (1985), Ferraro and Kreidlow (2004) were accomplished. The results indicate that even with the improvement in the rates, brazilian illiteracy remains high, unequal and reluctant. In addition, it was possible to highlight the role that the insufficiency of the institutionalized literacy process has on the production of illiteracy in school and general illiteracy, reflecting on the issues of access, permanence and quality of education.
Keywords: Illiteracy; Literacy; Illiteracy in school